Aeropolitics in East Asia: An institutional approach to air transport liberalisation. (January 2015) - Wang, James J.; Heinonen, Timo H.
Abstract: This article analyses the endogenous factors that influence the development of aeropolitics on the global scale, in general, and in East Asia, in specific. A mixed methods approach was used to uncover the relationships between factors related to institutional organisation and polity size, on the one hand, and aeropolitics, on the other. It is argued that, while the direct effects of geographical, demographic, and economic factors remain limited, the importance of the polity-level institutional framework to aeropolitics cannot be overstated. More precisely, economic institutions have a direct impact on the development of aeropolitics, whereas political institutions set the boundaries within which economic institutions operate. Highlights: We introduce an institutionally based approach to the study of aeropolitics. The effects of polity level variables on aeropolitics are quantified. We discover that politico-economic institutions dictate aeropolitical development. The effect of polity size on aeropolitical development remains limited.